SMART: an integrated planning and decision support tool for solid waste management - Lee, Chew Tin (Elsevier, 2014)
Solid waste management (SWM) system combined waste streams, waste collection, treatment and disposal methods are critically important to a regional, to achieve environmental economic and societal benefits. Decision-makers often have to rely on optimization models to examine a cost effective, environmentally sound waste management alternative. This paper presents a new systematic framework for long term effective planning and scheduling of SWM. This framework has been converted into software called Solid Waste Management Resource Recovery Tool (SMART). SMART is a first-of-a-kind SWM tool to facilitate the tradeoffs analysis between technical, economical, and environmental at national, regional, state, province, or community level. This simple tool is useful for decision makers for the selection of MSW technology including incineration, landfill, composting and recycling are while minimising the costs and meet CO2 reductions target. The developed tool was applied in Iskandar Malaysia as a case study.